Phosphate binder pill burden, patient‐reported non‐adherence, and mineral bone disorder markers: Findings from the DOPPS. Issue 1 (14th May 2015) - Fissell, Rachel B.; Karaboyas, Angelo; Bieber, Brian A.; Sen, Ananda; Li, Yun; Lopes, Antonio A.; Akiba, Takashi; Bommer, Jürgen; Ethier, Jean; Jadoul, Michel; Pisoni, Ronald L.; Robinson, Bruce M.; et al.
Abstract: Because of multiple comorbidities, hemodialysis (HD) patients are prescribed many oral medications, including phosphate binders (PBs), often resulting in a high "pill burden." Using data from the international Dialysis Outcomes and Practice Patterns Study (DOPPS), we assessed associations between PB pill burden, patient‐reported PB non‐adherence, and levels of serum phosphorus (SPhos) and parathyroid hormone (PTH) using standard regression analyses. The study included data collected from 5262 HD patients from dialysis units participating in the DOPPS in 12 countries. PB prescription ranged from a mean of 7.4 pills per day in the United States to 3.9 pills per day in France. About half of the patients were prescribed at least 6 PB pills per day, and 13% were prescribed at least 12 PB pills per day. Overall, the proportion of patients who reported skipping PBs at least once in the past month was 45% overall, ranging from 33% in Belgium to 57% in the United States. There was a trend toward greater PB non‐adherence and a higher number of prescribed PB pills per day. Non‐adherence to PB prescription was associated with high SPhos (>5.5 mg/dL) and PTH (>600 pg/mL). Adherence to PB is a challenge for many HD patients and may be related to the number of PB pills prescribed. Prescription of a simplified PB regimen could improve patient adherence and perhaps improve SPhos and PTH levels.